2015
DOI: 10.1002/ange.201508464
|View full text |Cite
|
Sign up to set email alerts
|

19F Paramagnetic Relaxation Enhancement: A Valuable Tool for Distance Measurements in Proteins

Abstract: Fluorine NMR paramagnetic relaxation enhancement was evaluated as a versatile approach for extracting distance information in selectively F-labeled proteins. Proof of concept and initial applications are presented for the HIV-inactivating lectin Cyanovirin-N. Single F atoms were introduced at the 4-, 5-, 6-or 7 positions of Trp49 and the 4 position of Phe4, Phe54 and Phe80. The paramagnetic MTSL label was attached to Cys residues that were placed into the protein at positions 50 or 52. 19 F-T 2 NMR spectra wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 36 publications
3
7
0
Order By: Relevance
“…Through the multi-technique data integration and contact map analyses, we identified long-range interactions involving residues S118 and I33 driving compactness within the ensemble and showed that S118 mutation mediates conformational changes and alters coactivator binding. Furthermore, through the means of fluorine-19 ( 19 F) NMR (Chrisman et al, 2018;Didenko et al, 2013;Kitevski-LeBlanc and Prosser, 2012;Li et al, 2010;Matei and Gronenborn, 2016), we show that mutations near residue I33 alter 19 F chemical shifts at the position of residue S118, thereby confirming the proposed metastable I33-S118 contact in the ensemble. Overall, our multi-technique biophysical approach allowed us to elucidate specific structural features of the ERa-NTD that mediate its transactivation function, and our findings raise important questions as to the potential of ''contact metastability'' to mediate functions for other nuclear receptors and/or IDPs in general.…”
Section: Introductionsupporting
confidence: 76%
See 1 more Smart Citation
“…Through the multi-technique data integration and contact map analyses, we identified long-range interactions involving residues S118 and I33 driving compactness within the ensemble and showed that S118 mutation mediates conformational changes and alters coactivator binding. Furthermore, through the means of fluorine-19 ( 19 F) NMR (Chrisman et al, 2018;Didenko et al, 2013;Kitevski-LeBlanc and Prosser, 2012;Li et al, 2010;Matei and Gronenborn, 2016), we show that mutations near residue I33 alter 19 F chemical shifts at the position of residue S118, thereby confirming the proposed metastable I33-S118 contact in the ensemble. Overall, our multi-technique biophysical approach allowed us to elucidate specific structural features of the ERa-NTD that mediate its transactivation function, and our findings raise important questions as to the potential of ''contact metastability'' to mediate functions for other nuclear receptors and/or IDPs in general.…”
Section: Introductionsupporting
confidence: 76%
“…To test the validity of the proposed I33-S118 interaction, we conducted 19 F NMR studies on the NTD by introducing a cysteine residue at the location of S118 to allow covalently linked 19 F labeling with a trifluoromethyl (-CF 3 ) group (depicted in Figures 7A and 7B). The 19 F labeling was achieved using 3-bromo-1,1,1-trifluoroacetone (BTFA), a widely used labeling reagent in 19 F NMR studies of both disordered and well-folded proteins (Didenko et al, 2013;Kitevski-LeBlanc and Prosser, 2012;Li et al, 2010;Matei and Gronenborn, 2016), with a more recent application to the nuclear receptor PPARg (Chrisman et al, 2018). Hereafter, we refer to the BTFA-labeled NTD S118C protein variant as NTD S118C -BTFA.…”
Section: Metastable Contact In the Idp Validated By 19 F Nmrmentioning
confidence: 99%
“…Its magnitude is described by the Solomon−Bloembergen equations 17 , 18 : where γ is the nuclear gyromagnetic ratio and J MF is the spectral density function accounting for the local side chain motions ( Supplementary Note ). Because PRE depends quadratically on the gyromagnetic ratio, it is weak for 13 C and 15 N nuclei but is significant for 1 H and 19 F 19 . Retrieving the distance-dependent paramagnetic component from the R 1 PRE for 1 H nuclei is difficult because of the interference from 1 H- 1 H cross relaxation 15 .…”
Section: Resultsmentioning
confidence: 99%
“…Recently, fluorine ( 19 F) NMR has regained attraction (Hellmich et al 2009 ; Liu et al 2012 ; Kim et al 2013 ; Kitevski-Leblanc et al 2013 ; Aramini et al 2014 ; Hoang and Prosser 2014 ; Manglik et al 2015 ; Matei and Gronenborn 2016 ; Lu et al 2019 ; Huang et al 2020 ). This spin is absent from virtually all biomolecules, however, 19 F probes can be artificially introduced into proteins by incorporation of fluorinated amino acids (Crowley et al 2012 ) or through post-translational modification with fluorine-containing tags (Brauer and Sykes 1986 ).…”
Section: Introductionmentioning
confidence: 99%